2021
DOI: 10.1016/s0958-2118(21)00029-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing a mesoporous hybrid organo-silica thin film prepared from an organic catalyst

Abstract: Silica material has limited hydrostability when it is produced as a thin film. In order to mitigate this restriction a modification strategy is needed. This article provides details of mesoporous hybrid organo-silica thin films that were successfully fabricated from a combination of a dual silicate precursor of tetraethyl orthosilicate/triethoxy vinyl silane, using organic catalysts. The research investigated the effect of calcination temperatures (350°C and 600°C) on the materials, and compared the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The siloxane formation is promoted by condensation reactions during the addition of base catalyst. Moreover, the organo catalyst (e.g., citric acid) also favoured the siloxane formation, in line with results reported by Sumardi, Elma, Rampun, Lestari, Assyaifi, Darmawan, Yanto, Syauqiah, Mawaddah and Wati [ 20 ] in the designing of mesoporous hybrid organo-silica using organo-catalyst with different silica precursors (TEVS). It may be assumed that the Si-OH bonds were reduced and converted to be other bonds such as Si-C, C≡C, etc.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The siloxane formation is promoted by condensation reactions during the addition of base catalyst. Moreover, the organo catalyst (e.g., citric acid) also favoured the siloxane formation, in line with results reported by Sumardi, Elma, Rampun, Lestari, Assyaifi, Darmawan, Yanto, Syauqiah, Mawaddah and Wati [ 20 ] in the designing of mesoporous hybrid organo-silica using organo-catalyst with different silica precursors (TEVS). It may be assumed that the Si-OH bonds were reduced and converted to be other bonds such as Si-C, C≡C, etc.…”
Section: Resultssupporting
confidence: 87%
“…The study published by Sumardi et al [ 20 ] investigated a mesoporous hybrid organo-silica thin film from organic catalyst. Instead of using TEOS as a silane precursor, this research combined dual precursor with TEVS to enrich the carbon into silica matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption saturation was achieved at 0.98–0.4 p/p o as the capillary condensation led to hysteresis. An earlier study [ 7 ] also reported the fabrication of silica xerogel that resulted in a mesoporous structure. The RTP method was also found to affect the resulting membrane thickness and the desalination performance.…”
Section: Resultsmentioning
confidence: 99%
“…High-performance inorganic membranes can be produced through a simple sol–gel process. However, the main issue of a silica membrane is weak hydro-stability [ 7 ] when in contact with water molecules. Hydro-stability is influenced by silanol groups (Si-OH) that typically form pores with a size of <1 nm [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology has long been a separation process in the industrial world because of its fast and efficient process [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In general, there are three types of membrane process that are usually applied, it is called reverse osmosis (RO), membrane distillation (MD), pervaporation and ultrafiltration [28].…”
Section: Introductionmentioning
confidence: 99%